Bourdieu and the fields of art in Australia: On the functioning of art worlds. (June 2013) - Herd, Nick
The study of the arts in Australia has paid insufficient attention to the structure of markets for art and the functioning of art worlds. This is despite the attention given by cultural economics to questions of artists employment and their welfare. The article starts from the concept of an 'art world' deployed by Becker, then considers the work of Bourdieu in the context of his place in the field of economic sociology. It mobilises the idea of markets as fields of structured exchange between agents in the field. It argues that the arts can be considered as an institutional field constituted as a series of markets. It proposes a framework for the study of these fields drawn from Van Maanen and considers how this could be applied to the performing arts in Australia.